Codependent no more : [compact disc, unabridged] : how to stop controlling others and start caring for yourself - Beattie, Melody (Recorded Books, 2005)
Where recovery begins for many people, this inspiring, straightforward, personal explanation of what codependency is and who has it gives listeners the option to change unhealthy behaviors and stressful relationships, as they rediscover hope, guidance, and encouragement.